Investigation of the Voltage Balance Scheme to Protect the Generator from Ground Fault - Abbasov, R.M.; Manafov, E.K.; Huseynov, F.H. (Herald of Azerbaijan Engineering Academy, 2023)
The article discusses the features of protecting the stator winding of the generator from ground faults using the voltage balance method. It has been established that this scheme can be used regardless of the generator load regime. The regimes of closing the generator winding to the ground for the voltage balance circuit at various Rf are considered. The simulation results carried out using the MATLAB SIMULINK software showed that the circuit is highly sensitive with ground fault resistances up to Rf = 3 kΩ. It was found that the voltage balance circuit provides protection for 70% of the generator stator winding.